Network Pharmacology-Based Strategy to Identify the Pharmacological Mechanisms of Pulsatilla Decoction against Crohn’s Disease - Liu, Jinguo; Zhang, Lu; Wang, Zhaojun; Chen, Shanshan; Feng, Shuyan; He, Yujin; Zhang, Shuo (Frontiers in Pharmacology, 2022)
Purpose: To explore pharmacological mechanisms of Pulsatilla decoction (PD) against Crohn’s disease (CD) via network pharmacology analysis followed by experimental validation. Methods: Public databases were searched to identify bioactive compounds and related targets of PD as well as related genes in patients with CD. Analyses using the drug–compound–target–disease network, the protein–protein interaction (PPI) network, and Gene Ontology (GO) and Kyoto Encyclopedia of Genes and Genomes (KEGG) enrichment analyses were performed to predict the core targets and pathways of PD against CD. Colon tissue resected from patients with CD and tissue samples from a mouse model of CD fibrosis treated with PD were assessed to verify the major targets of PD in CD predicted by network pharmacologic analysis. Results: A search of the targets of bioactive compounds in PD and targets in CD identified 134 intersection targets. The target HSP90AA1, which was common to the drug–compound–target–disease and PPI networks, was used to simulate molecular docking with the corresponding bioactive compound. GO and KEGG enrichment analyses showed that multiple targets in the antifibrotic pathway were enriched and could be experimentally validated in CD patients and in a mouse model of CD fibrosis. Assays of colon tissues from CD patients showed that intestinal fibrosis was greater in stenoses than in nonstenoses, with upregulation of p-AKT, AKT, p-mTOR, mTOR, p-ERK1/2, ERK1/2, p-PKC, and PKC targets. Treatment of CD fibrosis mice with PD reduced the degree of fibrosis, with downregulation of the p-AKT, AKT, p-mTOR, mTOR, p-ERK1/2, ERK1/2, and PKC targets. Conclusion: Network pharmacology analysis was able to predict bioactive compounds in PD and their potential targets in CD. Several of these targets were validated experimentally, providing insight into the pharmacological mechanisms underlying the biological activities of PD in patients with CD.